2009
DOI: 10.1007/s00423-009-0522-8
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of surgeon-performed ultrasound for primary hyperparathyroidism

Abstract: SUS to localize parathyroid adenomas is accurate and facilitates MIP. It provides substantial cost savings and patient convenience and should be the first diagnostic procedure performed for patients suspected to have pHPT. MIBI can be reserved for those patients in whom ultrasound has failed to localize a parathyroid gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 30 publications
0
28
2
Order By: Relevance
“…4,5 The outcomes of surgeon-based ultrasonography (SUS) in parathyroid disease have been reported from North America and Australasia though not from the UK. [6][7][8][9][10][11][12][13][14][15] The sensitivity of SUS of 60-89% reported in these studies is equivalent or superior to radiology-based ultrasonography (RUS) and SUS has now become a useful adjunct to parathyroid surgery in these countries.…”
mentioning
confidence: 97%
“…4,5 The outcomes of surgeon-based ultrasonography (SUS) in parathyroid disease have been reported from North America and Australasia though not from the UK. [6][7][8][9][10][11][12][13][14][15] The sensitivity of SUS of 60-89% reported in these studies is equivalent or superior to radiology-based ultrasonography (RUS) and SUS has now become a useful adjunct to parathyroid surgery in these countries.…”
mentioning
confidence: 97%
“…There is a learning curve associated with SUS. Arora et al [48] mentioned that they confirmed their SUS with MIBI for the first 250 patients, to complete the learning curve. In our method we think that only ten cases are enough for a learning curve, because we perform US in the presence of a radiologist, not a surgeon alone.…”
Section: Discussionmentioning
confidence: 97%
“…The detection of concomitant thyroid nodules that may need fine needle aspiration biopsy may help to prepare the patient and surgeon to deal with this pathology. Ultrasound is also more cost-effective than sestamibi scanning [9] . Sestamibi remains a valuable resource in the diagnosis of primary hyperparathyroidism, but should be reserved for cases where ultrasound gives equivocal results.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is a rapid technique for surveying the anterior compartment of the neck, but questions remain regarding the operator's effect on resultant sensitivity [9,10] . Therefore, the goals of this study were to independently evaluate both neck ultrasonography and sestamibi as single-modality screening tools for the localization of hyperactive parathyroid glands in primary hyperparathyroidism, and to evaluate the effects of cervical ultrasonography operator variability on subsequent findings.…”
Section: Introductionmentioning
confidence: 99%